Recollections of past days : the autobiography of Patience Loader Rozsa Archer - Archer, Patience Loader, 1827-1921 (Life writings of frontier women ;, 2006)
Volume 8, Life Writings of Frontier Women series. For visitors to the Martin's Cove historic site in Wyoming, Patience Loader has become an icon of the disastrous winter entrapment of the Martin and Willie handcart companies. Her record of those events is important, but there is much else of interest in her autobiography. In fact, it is a bit unusual that someone such as her would have left such an engaging record of her life.